Efek Karakteristik Dewan Terhadap CSR Disclosure - Devika Febyanti; Endah Susilowati; Helmy Wahyu Sukiswo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Corporate Social Responsibility (CSR) disclosure is inseparable from companies whose production activities are directly related to Natural Resources (SDA). There are many factors that are considered to be able to influence CSR disclosure, one of which is the characteristics of board members (board expertise, board diversity culture, board education). This study seeks to explain how these aspects are related so that they can influence the company's CSR disclosure. Quantitative techniques are used in testing and analyzing written research using annual reports and sustainability reports of mining sector companies listed on the IDX in 2020-2022. The sampling technique in written research is purposive sampling and a sample of 17 companies was obtained. The Partial Least Square (PLS) method was applied to analyze data with the SmartPLS 3 program. The results of the research analysis prove that board expertise, board diversity culture, board education are able to influence the company's CSR disclosure.